2019
DOI: 10.2134/cftm2018.11.0094
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Irrigation Rates and Frequency for Perennial Ryegrass in Western Oregon

Abstract: Irrigation applied at a rate of 3.0 inches per month (0.75 inches per week) from July to September will provide improved perennial ryegrass turf quality and percent green cover in western Oregon.• Replacing 45 to 49% evapotranspiration is adequate to maintain acceptable turfgrass quality in this environmental zone.• Three inches of irrigation per month (0.75 inches per week) will provided perennial ryegrass turf quality and percent green cover equivalent to great irrigation amounts.• Eight irrigation applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Results regarding ET ref replacement in this study concurred with results reported by Fry and Butler (1989), who determined that tall fescue required less ET ref replacement than hard fescue. Olsen, Cain, Gould, Mattox, and Kowalewski (2019) found that perennial ryegrass could be maintained in western Oregon at 45–49% ET ref replacement. Richardson, Karcher, Hignight, and Hignight (2012) found that 21–32% ET ref replacement was required to keep tall fescue cultivars at 40% green cover, while 14 to 28% ET ref replacement was required for Kentucky bluegrass cultivars in Albany, OR, when maintained at 1 inch.…”
Section: Reference Evapotranspiration Replacementmentioning
confidence: 99%
See 2 more Smart Citations
“…Results regarding ET ref replacement in this study concurred with results reported by Fry and Butler (1989), who determined that tall fescue required less ET ref replacement than hard fescue. Olsen, Cain, Gould, Mattox, and Kowalewski (2019) found that perennial ryegrass could be maintained in western Oregon at 45–49% ET ref replacement. Richardson, Karcher, Hignight, and Hignight (2012) found that 21–32% ET ref replacement was required to keep tall fescue cultivars at 40% green cover, while 14 to 28% ET ref replacement was required for Kentucky bluegrass cultivars in Albany, OR, when maintained at 1 inch.…”
Section: Reference Evapotranspiration Replacementmentioning
confidence: 99%
“…Olsen et al. (2019) found that twice a week irrigation produced acceptable perennial ryegrass turf quality in western Oregon. Results regarding irrigation interval in this study concurred with results reported by Fry and Butler (1989), who determined that tall fescue could go longer between irrigation events than hard fescue without compromising turf quality.…”
Section: Irrigation Intervalmentioning
confidence: 99%
See 1 more Smart Citation
“…In July, August and September plots receiving irrigation four times per week (both ET ref replacement and 0.6 cm) had the highest TQ ratings, while plots that received 2.4 cm monthly or no irrigation had the lowest TQ ratings (Table 3). Interestingly, plots receiving 2.4 cm of irrigation monthly had greater TQ in Sept compared to no irrigation, despite similar TQ ratings in June, July, and Aug. Olsen et al (2019) found that 0.6 cm applied four times per week provided minimally acceptable TQ. Improved TQ in September 2018 and 2019 on monthly irrigation plots compared to no irrigation suggest that applying some water is better than not applying any, and may reduce drought recovery time.…”
Section: Resultsmentioning
confidence: 88%
“…Irrigation treatments include; a non‐irrigated control, 0.6 cm applied four times per week, 80% ET ref replacement calculated from an on‐site weather station (AgriMet Weather Station) applied four times per week, and 2.4 cm applied once per month. Irrigation treatments were applied from mid‐June to mid‐September with four 5Q MPR fixed spray nozzles per 1.5 m by 1.5 m plot (Olsen et al., 2019). Plots were mowed weekly at 5.0 cm, and received 9.8 g N m –2 yr –1 .…”
Section: Methodsmentioning
confidence: 99%